Natural science education in the university core curriculum - D. N. Kyrov; N. V. Nesterova; O. A. Prituzhalova; L. D. Cheremnykh (Russian State Vocational Pedagogical University, 2024)
Introduction. One of the current issues in the theory and methodology of higher education is the development of its content that responds to societal challenges. Specialist training in any field of professional activity necessarily includes a natural science component, as it reflects the achievements and problems of scientific and technological progress. Against the backdrop of a paradigm shift in education, universities are transitioning to individual educational trajectories to accommodate the needs of an individual in the process of continuous professional development. Individual educational trajectories include both core (compulsory) and elective courses. The subject of this study is natural science education as a mandatory component of the curriculum at a classical university.Aim. The aim of the study was to analyse the changes in the forms of natural science knowledge transfer in the context of implementing individual educational trajectories in higher education.Methodology and research methods. As the main research methodology, an axiological approach with elements of a personality-oriented approach was used. The study analyses the changes in the content and forms of teaching a natural science course at the university within the framework of individual educational trajectories. The results of a student survey were analysed after completing the course.Results and scientific novelty. In the course of the study, the forms of classes and control were determined that are suitable for joint education of students of natural sciences and humanities in the context of transition to individual educational trajectories. The methods of teaching a natural science discipline have been selected, allowing the integration of soft skills into the educational process to be achieved. As an important learning outcome, it is possible to record an increase in the digital competencies of students and teachers in terms of using jointly edited cloud files, resources for online discussions and testing, as well as the inclusion of students in joint interdisciplinary projects and the development of communication practices. When evaluating the introduction of the discipline, most students noted the benefits of expanding their horizons, making new friends and acquaintances, and forming a critical view of the world. The students named discussions, games and group presentations as the preferred forms of the lesson.Practical significance. An innovative course has been created that allows students within individual trajectories to see the potential of modern natural sciences and to engage in collaborative interdisciplinary projects.